Tralokinumab in atopic dermatitis. (13th August 2021) - Wollenberg, Andreas; Weidinger, Stephan; Worm, Margitta; Bieber, Thomas
Summary: Atopic dermatitis (AD) is a common chronic inflammatory disease characterized by recurrent eczematous lesions and intense pruritus, and it can have marked negative impact on those affected. Pathophysiologically, AD is complex with genetic predisposition and environmental provocation being important contributors. Mechanistically these can promote epidermal barrier dysfunction, skin microbiome abnormalities and a skewed immune response which is predominantly type‐2 immunity‐based. Our increased understanding of the immunological processes involved highlight a key role for interleukin‐13 (IL‐13). This mini‐review evaluates tralokinumab, a high‐affinity monoclonal antibody that specifically binds to and inhibits IL‐13. Based on dose‐finding study results, tralokinumab 300 mg every two weeks (Q2W) subcutaneously (SC) was investigated in three pivotal phase III clinical trials in adults with moderate‐to‐severe AD not adequately controlled on topical corticosteroids alone. Tralokinumab was significantly superior to placebo regarding the proportion of patients achieving IGA 0/1 and EASI‐75 at week 16 (primary endpoints), as well as improving scores for worst daily pruritus, Dermatology Life Quality Index (DLQI), and Scoring Atopic Dermatitis (SCORAD) (secondary endpoints). The week 16 response was sustained during follow‐up, and treatment with tralokinumab was found to be well‐tolerated with an overall frequency and severity of adverse events comparable to placebo.